Regional Differentiation of Emissions and Risk Perception of Dust-Related Morbidity - Roza Kamilova, Ibratjon Karimov, Raushan Ataniyazova, Madinabonu Azimova, Aqkerbez Baynazarova (South Eastern European Journal of Public Health, 2025)
The article presents an analysis of regional differentiation of pollutant emissions into the atmospheric air of the Republic of Uzbekistan for a five-year period, as well as the results of a study of the subjective opinion of the population of Termez on the factors affecting their health, including dust-related diseases. It was found that the greatest contribution to air pollution is made by the Tashkent region (28.1% of the total emissions) and the city of Tashkent (14.4%). At the same time, the results of a questionnaire survey of the population of Termez showed that, despite the relatively low level of air pollution in the Surkhandarya region, the subjective perception of environmental risks remains high.